Prioritizing rapid COVID-19 testing in emergency general surgery patients decreases burden of inpatient hospital admission - Heather Carmichael; Catherine G Velopulos; Madeline B Thomas; Madison Harrison; Danielle Abbitt; Allison Moore; Quintin W O Myers (Trauma Surgery & Acute Care Open)
Objectives The COVID-19 pandemic has changed delivery of emergency general surgery (EGS) and contributed to widespread bed shortages. At our institution, rapid testing is not routinely approved for EGS patients. We examined common EGS conditions (appendicitis and acute cholecystitis), hypothesizing that necessity of testing for COVID-19 significantly delayed operative intervention.Methods We performed a prepost study to examine a 2-month timeframe, or historical control, prior to COVID-19 testing (January 1, 2020–March 1, 2020) as well as a 2-month timeframe during the COVID-19 era (January 1, 2021–March 1, 2021). We chose conditions that are frequently treated surgically as outpatient or observation status. We examined time for COVID-19 test to result, and associated time to operative intervention (operating room (OR)) and need for admission.Results Median time to COVID-19 test results was 7.4 hours (IQR 5.8–13.1). For appendectomy, time to surgical consultation or case request did not differ between cohorts. Time to OR after case request was significantly longer (12.5 vs 1.9 hours, p<0.001) and patients more frequently required admission prior to operative intervention if receiving treatment in the COVID-19 timeframe. Similarly, for cholecystectomy there were no differences in time to surgical consultation or case request, but time to OR after case request was longer in the COVID-19 era (21.1 vs 9.0 hours, p<0.001).Conclusion While COVID-19 positivity rates have declined, the purpose of this study was to reflect on one element of our hospital system’s response to the COVID-19 pandemic. Based on our institutional experience, waiting for COVID-19 test results directly impacts time to surgery, as well as the need for admission for a historically outpatient procedure. In the future, if the healthcare system is asked to respond to another pandemic or similar situation, expediting time to OR to eliminate unnecessary time in the hospital and non-critical admissions should be paramount.Level of evidence Level III, prognostic/epidemiological.